2013
DOI: 10.1371/journal.pone.0076001
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Role of Brain Derived Neurotrophic Factor Genetic Variation in Alzheimer’s Disease Neurodegeneration

Abstract: There is accumulating evidence that neurotrophins, like brain-derived neurotrophic factor (BDNF), may impact aging and Alzheimer’s Disease. However, traditional genetic association studies have not found a clear relationship between BDNF and AD. Our goal was to test whether BDNF single nucleotide polymorphisms (SNPs) impact Alzheimer’s Disease-related brain imaging and cognitive markers of disease. We completed an imaging genetics study on 645 Alzheimer’s Disease Neuroimaging Initiative participants (ND=175, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 43 publications
2
40
0
3
Order By: Relevance
“…15,20,21 However, in one of these studies, the authors reported relationships between greater BDNF expression in the dorsolateral prefrontal cortex and slower cognitive decline. 21 Another group did not find associations with the polymorphism but noted that greater serum BDNF levels resulted in reduced dementia and AD incidence.…”
Section: C-pittsburgh Compound B-pet Neuroimaging Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…15,20,21 However, in one of these studies, the authors reported relationships between greater BDNF expression in the dorsolateral prefrontal cortex and slower cognitive decline. 21 Another group did not find associations with the polymorphism but noted that greater serum BDNF levels resulted in reduced dementia and AD incidence.…”
Section: C-pittsburgh Compound B-pet Neuroimaging Protocolmentioning
confidence: 99%
“…20 Finally, a third report did not find associations with the Val66Met polymorphism but did with other BDNF SNPs, specifically rs1157659, rs11030094, and rs11030108. 15 These discrepancies underscore the need for further understanding of the intricacies in the relationship between BDNF polymorphisms, BDNF expression, and cognitive function.…”
Section: C-pittsburgh Compound B-pet Neuroimaging Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF polymorphism Val66Met modulates integration of neurons in vivo and regulates episodic memory and hippocampal physiological activation in humans [Egan et al, 2003; McDole et al, 2015]. Moreover, genetic variation in BDNF associated with hippocampal atrophy and cognitive decline have been identified using neuroimaging-genetics methods [Honea et al, 2013]. Pro-inflammatory cytokine IL-6 plays an important role in the formation of new neurons and glial cells from neural progenitor cells during adult neurogenesis, and IL-6 variations have been associated with AD, multiple sclerosis, and severe traumatic brain injury [Schmidt et al, 2003; He et al, 2010; Dalla Libera et al, 2011; Erta et al, 2012].…”
Section: Modulators Of Adult Neurogenesismentioning
confidence: 99%
“…Нейротрофический фак-тор мозга (BDNF) играет очень важную роль как в раз-витии, так и пластичности мозга. В настоящее время уровень BDNF рассматривают в качестве одного из базовых маркеров нейродегенерации [18,13], что ставит вопрос о возможном влиянии депрессии на течение шизофренического процесса. Изучение это-го вопроса не только имеет теоретическое значение, но и представляется важным с позиции обоснования подходов к терапии данной категории пациентов.…”
Section: оригинальные исследованияunclassified